Sistem Penentuan Supplier Kawat Las Dengan Metode Analitycal Hierarchy Process (AHP) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Gina Ramayanti; Hidayatul Ulum (Jurnal Sistem dan Manajemen Industri, 2017)
Supplier selection is being a strategic activity, especially when the supplier is supplying materials that will be used in the long term. In the world of construction, one part of the supply chain which has a significant contribution to the improvement of the company's effectiveness is the efficiency in the procurement of materials (raw materials) from suppliers. In the research found the problem of 50 TON of welded wire failed. This study aims to determine the criteria based on the company needs in determining the supplier of welding wire and provide the ranking of suppliers as a material consideration in determining the supplier. The study used the Analytical Hierarchy Process (AHP) method for the selection of criteria and the Technique For Order Performance By Similiar To Ideal Solution for rating or evaluating alternative suppliers. Based on the results of AHP calculation we get the weight of each criteria as follows, for the quality of 0.0644, the price 0.056, the delivery time of 0.158, the quantity 0.053, the response to the claim of 0.093, and from the criteria are made reference to the calculation of vendor selection using TOPSIS. Results obtained supplier S2, i.e., PT.Esabindo Pratama ranked first as a priority supplier with a preference value of 0.322. Excellence which is owned by supplier S2 (PT.Esabindo Pratama) are the criteria of quality, price, quantity